HIV prevalence in Africa : validity of a measurement - (:unkn) unknown (My University, 2007)
HIV national prevalence is estimated, in sub-Saharan Africa, from two main data sources : sentinel surveillance of pregnant women and national population-based surveys (DHS). In several countries, results differ, questioning each of those approaches' efficiency. What range, limitations and objective significance can be granted to the diverse observations, each apprehending the real from a different point of view ? DHS constitute a good indicator of prevalence levels at a national or a regional scale. Intraregional variations can be reproduced by using spatial analysis techniques. But DHS frequencies are inaccurate to measure short-term evolution. Sentinel surveillance, local estimator of magnitude of epidemics, can be a tendency indicator under certain conditions. However, if the present situation is only just starting to be better-known, a real measurement of HIV dynamics is still out of our reach.
Keywords: African Research